Analisis Kesalahan Penyusunan Judul PTK sebagai Dasar Ketepatan Arah Penelitian - Silvi Nur Dina; Hani Amaria; Ichlasul Amalia; Siti Amanda; Imron Fauzi (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
This study aims to identify errors in the formulation of Classroom Action Research (CAR) titles, analyze the patterns of errors that emerge, and explain their impact on the direction of the research. The study employed a Systematic Literature Review (SLR) method, with data sources obtained from the Google Scholar and Scopus databases. The selection process involved the stages of identification, screening, eligibility assessment, and inclusion, resulting in 11 relevant articles. Data analysis was conducted qualitatively through data reduction, data presentation, and drawing conclusions. The results indicate that errors in formulating CLR titles can be classified into three categories: structural, substantive, and linguistic errors. The most frequently identified errors include unclear actions in the title, the use of overly general variables, and the use of ineffective language. These errors result in inaccuracies in the research direction, such as inconsistencies between the title and the research problem, objectives, and methods. Therefore, the formulation of PTK titles must be done carefully, clearly, and specifically to accurately reflect the research content and support the coherence among research components.